Modified resol type phenolic resin nanocomposites as surface metal coatings. (23rd February 2021) - Ahmed, Sahar; Mohamed, Moshera; Mansour, Nahla; El‐Komy, Doaa; Sadek, Elham
Abstract: Nanocomposites based on resol resin as a matrix and prepared organoclay, from Egyptian bentonite clay, as reinforcement material were synthesized. The effect of organoclay content (i.e., 0.5, 1.0, 1.5, 2.0, and 2.5 phr) on the properties of the prepared samples with respect to the prepared composites and resol resin with no clay was investigated. The prepared samples with higher organoclay content (i.e., 2.0 phr) were modified with epoxy or/and urethane resin and characterized using transmission electron microscope (TEM), X‐ray diffraction (XRD), and Fourier transform infrared measurements (FTIR). TEM showed uniform dispersion of the clay while XRD showed exfoliated structures. FTIR measurements confirmed the bond formation between epoxy or/and diisocynate with phenolic hydroxyl groups of resol resin. Mechanical properties, chemical resistance, thermal properties, and electrical volume resistivity were studied. Results showed that epoxy modified resol resin film samples with 2.0 phr organoclay exhibited higher adhesion and scratch hardness values, higher chemical resistance, thermal stability, and lower electrical conductivity compared with mixed epoxy/urethane and urethane samples as well as unmodified resol resin nanocomposite film samples. The samples could be useful as surface metal coatings. Abstract :